Analisis Spasial dan Temporal Sebaran Suhu Permukaan Laut di Perairan Sumatera Barat - Alfajri Alfajri; Mubarak Mubarak; Aras Mulyadi (Dinamika Lingkungan Indonesia, 2017)
This study was conducted on March-April 2016 in West Sumatra Waters. This study aimed to know distribution and sea surface temperature fluctuation daily and monthly in West Sumatra Waters and to know the factor that influences distribution and fluctuation of sea surface temperature in West Sumatra Waters. Sea surface temperature has taken from 3 stations which: Pariaman Waters, Padang-Pariaman Regency Waters and Bungus Waters, Padang. The result of daily data sea surface temperature by Aqua-Modis from 15 February, 20 February, 25 February, 2 March, 7 March and 12 March 2016 On West Sumatra Waters showed that the highest sea surface temperature was 34,54°C occured on 15 February and the lowest was 27,41°C on 12 March 2016. Average of monthly sea surface temperature on April 2015-March 2016 was about 27,07-34,98°C. The highest sea surface temperature occured on February and March 2016 and the lowest occurred on April and October 2015. Based on observation of monthly sea surface temperature knowed that sea surface temperature on western season increased and sea surface temperature and eastern season decreased. Observation showed that sea surface temperature influence by water mass moved because muson wind. Water mass moved impact to distribution of sea surface temperature on waters. The high or low of sea surface temperature in waters estimated because of sunlight intensity and rain on waters. As high the sunlight intensity to the waters so sea surface temperature on waters will increased and as high the rain so the sea surface temperature will decreased. El Nino phenomenon that occurred on February and March 2016 because sea surface temperature on that month was increased.